The use of hyaluronic acid in individuals with cleft lip and palate: Literature review - Kelly Fernanda Molena; Lidiane de Castro Pinto; Gisele da Silva Dalben (Wolters Kluwer Medknow Publications, 2021)
Since the Resolution 198/2019 of Brazilian Dental Council, which regulates orofacial harmonization as a dental specialty, and the advent of various uses of facial fillers, such as hyaluronic acid (HA), it is possible to perform both esthetic and functional corrections in individuals. Individuals with cleft lip and palate (CLP) present lip irregularities even after orofacial rehabilitation with an interdisciplinary team with several corrective surgeries, interfering with the esthetics, which can cause problems in self-esteem and social insertion. Thus, facial filling is an innovation that, together with dentistry, contributes to the individual's esthetics and well-being. Considering the patient safety and health, more research is progressively being conducted to make such procedures less invasive. This work conducted a literature review on the use of HA as a facial filler to correct lip scars in patients with CLP. By a literature and transverse search in Scientific Electronic Library Online and PubMed databases using specific descriptors, the studies that met the inclusion criteria were selected, from 1990 to 2020. It can be concluded that the use of HA as a facial filling material in the correction of lip scars from reparative surgeries related to CLP has been shown to be effective both for correction of facial asymmetry and to improve the quality of life of patients who used the procedure.